Research for action cross-national perspectives on connecting knowledge, policy, and practice for children - Chaskin, Robert J.; Rosenfeld, Jona M. (Jona Michael), 1922- (Oxford : Oxford University Press, 2008)
This book builds up a cross-case analysis that distills lessons, throws enduring questions into relief, and lays a foundation for informing future practice. It mines the cross-national experience to develop perspective for a better understanding of the importance of different policy and cultural environments.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child welfare -- Cross-cultural studies; Children -- Services for -- Cross-cultural studies